CULTURAL AND VALUE CONCEPTS IN ORATORY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article explores the profound influence of cultural and value concepts on oratory, shedding light on how diverse cultures shape the art of persuasive speech. By analyzing literature and employing various research methods, the article highlights the significance of understanding cultural nuances in oratory. The results demonstrate that cultural and value concepts deeply impact speech construction and reception, offering valuable insights for effective cross-cultural communication. The discussion delves into the implications of these findings, emphasizing the need for cultural sensitivity in oratory. In conclusion, the article underscores the importance of recognizing and respecting diverse values when engaging in persuasive communication, offering practical suggestions for orators to enhance their cross-cultural effectiveness.